Analysis of clinical characteristics and influencing factors of fever after electroconvulsive therapy: a retrospective study from the Chinese population - Zhang, Mengmeng; Xu, Rui; Wang, Juan; Wu, Chunyan; Ren, Huicong; Zhang, Zhaohui; Li, Juan (Frontiers in Psychiatry, 2025)
BackgroundAlthough well-established as a first-line treatment for psychiatric disorders, electroconvulsive therapy (ECT) carries risks of adverse effects, including fever. The purpose of this study was to elucidate the incidence, clinical characteristics, and risk factors related to fever after ECT.MethodsWe retrospectively analyzed medical records of patients receiving ECT at the Second Affiliated Hospital of Xinxiang Medical University (April 2019–January 2020). Patients were subsequently divided into two groups: a fever group, in which the body temperature was ≥ 38°C; and a non-fever group, in which the body temperature was <38°C.ResultsA total of 895 patients underwent 7801 units of ECT treatment. Fever was analyzed at the patient and treatment unit level. At the patient level, 104 out of 895 patients (11.6%) experienced at least one fever within 24 hours after ECT, Compared with the non-fever group, the fever group showed statistically significant differences in age, gender, types of psychiatric ward (closed or open), and anesthetic type (all P < 0.05) but not in the total number of ECT units or diagnoses, Logistic regression analysis identified the risk variables for fever as younger age (≤ 29), closed psychiatric ward, etomidate administration, and being male; and at the treatment units level, among the 7,801 ECT units, fever occurred in 129 units (1.7%), with a median maximum temperature of 38.5 (38.0–40.3)°C. Following ECT, 55.8% (72/129) of the fever unit temperatures returned to normal body temperature as assessed by clinical observation or cooling measures, whereas 44.2% (57/129) required cooling combined with antibiotics. Compared to baseline, the fever units had higher white blood cell and neutrophil counts (P < 0.001) but lower lymphocyte counts (P < 0.001). In 79.8% (103/129) of the units, the fever was observed during the first 5–8 hours after the ECT treatment was completed, with 94.6% (122/129) of the units returning to normal body temperature within 24 hours of treatment. Only 5.4% (7/129) of the units opted to discontinue ECT treatment due to fever.ConclusionWe found that fever after ECT requires attention in clinical practice. Although the direct impact of fever after ECT treatment is limited, given its potential risks, it is advised to focus on strengthening the temperature monitoring of high-risk groups.